Visual landscape evaluation of tourism areas in West Java, Indonesia based on Trisakti University employees' perspectives - Ina Krisantia, (2012)
In landscape, visual aspects are very important and contribute to our regional identity, while also giving value to the environment. In Indonesia, there are many tourism areas that are losing their visual attractiveness due to rapid development. This situation will affect the value of visual landscape. Based on this situation, it is imperative for visual landscape to be preserved. This study intends to evaluate visual landscape with an emphasis on preference, meaning, and economic value in relation to its preservation. This study uses a public preference method and as well as contingent valuation. 204 respondents were selected through convenience sampling among members of the public in Trisakti University to participate in a survey, where they were asked to rate their preference based on 50 photographs of landscapes in several tourism areas of Indonesia. They were required to provide their reasons for preference in closed and open-ended descriptions by choosing 5 scenes they preferred most and also rate their willingness to pay to preserve the scene. The results found that there were three categories of preferred scenes with Resort and Highland scenes exhibiting a high preference, while Beach scenes having a moderate preference. The most preferred scenes were those of Highland landscape, which are considered to be strong in mystery, the meaning of serenity due the experience such as tranquility,smoothness through the ground texture from lawns. To preserve visual landscape in the highland category, the mean amount respondents were willing to pay was $USD 10.85 (RP108.550,-). There were relationships between preference, meaning, and willingness to pay with a positive relationship between preference and meaning showing a significant correlation. There was a negative relationship between preference and willingness to pay because the quantity of experience increases with landscape quality, and that causes utility to diminish. There was also a positive relationship between willingness to pay and meaning. In terms of meaning, meanings such as complexity contributed to preference of people for scenes in the highland and beach category, while coherence contributed to people’s preference of scenes in the resort category. Besides that, the meaning of mystery contributed to Willingness to Pay in the highland category, while legibility contributed to the Willingness to Pay in the resort category. Therefore, it can be concluded that people preferred scenes from the highland and beach category because of the complexity offered in the scenes, while preference for scenes from the resort category was due to the meaning of coherence. In addition, people had the tendency to pay for the preservation of scenes from the highland category because of the mystery and legibility associated with scenes from resort category. Without doubt, this research has a big potential to create a model to evaluate visual landscape and in the same time it gives visual value to preserve the scenes in tourism areas.